Study of recycling potential of solid waste of tourist area in Pariaman City. (August 2019) - Aziz, R; Mira,
Abstract: This study aims to measure and analyze the data of solid waste generation, composition and recycling potential of the tourist area of Pariaman City. Sampling and determination of samples based on SNI 19-3964-1994. Sampling location was on three beaches in Pariaman City were Gandoriah Beach, Cermin Beach, and Kata Beach, and one island namely Angso Duo island. The results showed that the average unit of solid waste generation was 0.033 kg/cap./day or 0.344 liters/cap./day. The largest component of the waste was organic waste by 90.79%, while inorganic waste by 9.21%. Recycling potential consists of non-ferrous metal 95.072%, plastic 93.359%, glass 64.505%, food waste 36.787% and paper waste 19.231%. It was recommended that solid waste could be treated by composting technology to treat the garbage, cleaning and packing the rubbish, and utilizing the waste that has value to produce the creative product for supporting the tourism activity such as souvenirs.